2019
DOI: 10.1177/1120700019858335
|View full text |Cite
|
Sign up to set email alerts
|

Does vitamin E highly-crosslinked polyethylene convey an advantage in primary total hip replacement? A systematic review and meta-analysis

Abstract: Background: Vitamin E highly cross-linked polyethylene (HXLPE) was developed to reduce wear in total hip replacement (THR). This formal systematic review and meta-analysis aimed to provide independent synthesis of wear characteristics of Vitamin E treated HXLPE compared to HXPLE/UHMWPE. Secondary outcome measures were differences in revision rates and functional scores. Methods: We performed a formal syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…Various cross‐linked polyethylene materials have been applied in THAs that greatly enhanced the wear resistance of the polyethylene liner but with lower mechanical strengths compared to conventional polyethylene liner materials . Our data indicate that for a fixed cup size or outer polyethylene liner diameter, the relationship between the contact area and stress is nonlinear, as depicted in Figure A,B.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Various cross‐linked polyethylene materials have been applied in THAs that greatly enhanced the wear resistance of the polyethylene liner but with lower mechanical strengths compared to conventional polyethylene liner materials . Our data indicate that for a fixed cup size or outer polyethylene liner diameter, the relationship between the contact area and stress is nonlinear, as depicted in Figure A,B.…”
Section: Discussionmentioning
confidence: 78%
“…Although recent studies on highly cross‐linked polyethylene liners showed reduced liner wear and therefore improved implant longevity, whether or how the wear rate depends on structural parameters still remains not to be fully understood. Clinical studies have reported the effect of metal head sizes on polyethylene liner wear using liner retrievals from patients and reported that increased femoral head size was associated with increased volumetric wear .…”
Section: Discussionmentioning
confidence: 99%
“…The general concern with higher activity level after THA is polyethylene wear. As noted previously, however, polyethylene durability has improved significantly over the past few decades [ [31] , [32] , [33] ]. In a registry analysis, highly crosslinked polyethylene had a 16-year cumulative revision rate of 6.2%, whereas conventional polyethylene had a revision rate of 11.7% [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The process of crosslinking produces free radicals that can be trapped within the polyethylene [ 34 ]. Antioxidant additives, such as vitamin E, have been added to polyethylene manufacturing to neutralize free radicals and improve polyethylene wear [31] , [32] , [34] , [35] . The polyethylene evaluated in this study is highly crosslinked and vitamin E infused.…”
Section: Discussionmentioning
confidence: 99%
“…Extended reviews have been published about XLPE including vitamin E or other antioxidants [16,17], but to date, main data are collected from ex vivo experiments or clinical studies with less than 5-year follow-up. At this short term, vitamin E poly has not proved any clinically significant advantage in terms of patient function, wear or revision rate as compared to first generation of XLPE.…”
Section: Long-term Wear Osteolysis and Survivorshipmentioning
confidence: 99%